1973
DOI: 10.1037/h0035103
|View full text |Cite
|
Sign up to set email alerts
|

Preferred seating position and distance in various situations.

Abstract: The preference of 30 students for 4 seating positions in counseling, formal, home, and 2 social situations and the preferred distance between chairs in the various seating positions were investigated. The subjects were required to indicate their preference for position and distance of furniture as depicted on photographs. Relationships between these preferences and personality variables also were investigated. Results showed preference for different seating positions in some situations although similarities oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
1
18
1
Order By: Relevance
“…to 1.5 m (60 in.) (Broekmann & Moller, 1973;Dinges & Oetting, 1972;Knight & Bair, 1976;Lassen, 1973;Lecomte, Bernstein, & Dumont, 1981;G. L. Stone & Morden, 1976).…”
Section: Furniture and Room Designmentioning
confidence: 99%
See 1 more Smart Citation
“…to 1.5 m (60 in.) (Broekmann & Moller, 1973;Dinges & Oetting, 1972;Knight & Bair, 1976;Lassen, 1973;Lecomte, Bernstein, & Dumont, 1981;G. L. Stone & Morden, 1976).…”
Section: Furniture and Room Designmentioning
confidence: 99%
“…In a related area, Haase and DiMattia (1970) and Broekmann and Moller (1973) found that differences existed between counselors and clients in preferences for seating arrangements. It is interesting that these researchers reported that clients preferred more protected furniture layouts, such as formal arrangements (counseling across a desk), than did counselors.…”
Section: Furniture and Room Designmentioning
confidence: 99%
“…During lengthy conversations, the use of chairs, together with tables/desks, can affect physiological and psychological comfort, length and breadth of discourse, perceptions of counsellor and level of anxiety (Lecomte, Bernstein, & Dumont, ; Sommer, ). Without exception, studies indicated that in formal contexts people prefer sitting at an intermediate distance (1.2–1.5 m) from each other, with participants engaging in more lengthy monologues and reporting lower anxiety and greater comfort (Broekmann & Moller, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that the furniture arrangement in a situation of interpersonal interaction may have a significant influence on cIients' perceptions of the situation and may influence their subsequent behavior (Broekmann & Moller, 1973). Haase and DiMattia (1970) reported that the most prqferred position depicts the participants interacting over the corner of a desk.…”
Section: Seating Arrangementsmentioning
confidence: 99%
“…Such findings might offer grounds for speculation about the client's reaction to being maneuvered into an interaction where the furniture arrangement is suited to the counselor (i.e., no desk intervening) and not to the feelings, and perhaps the benefit, of the client. Furthermore, clients may prefer a relatively formal seating arrangement (an intervening desk) under unfamiliar circumstances, whereas a more informal position may be preferred under more familiar circumstances (Broekmann & Moller, 1973).…”
Section: Seating Arrangementsmentioning
confidence: 99%